Karakter Busana Kebesaran Raja Surakarta dan Yogyakarta Hadiningrat Periode 1755-2005 - Ngatinah Ngatinah (Journal of Visual Art and Design, 2008)
Clothes represent cultural expressions and associate with certain social status. The Javanese societies, as complex as they are, possess unique social stratification according to the hierarchy of their positions, where the king has the tipmost status, followed by the nobles, merchants, farmers, and commoners. Thus, king clothes expresses societal status and cultural heritage of Java. This paper explores varieties of king clothes from the Surakarta and Yogyakarta kingdom on the period of 1755-2005, in order to identify the styles, associated symbolic meanings, and aesthetic values of the clothes whose patronage the Javanese people. The study focuses on the objects associate with king's clothes such as throne (kuluk/panunggul), sikepan bleggen, bordiran ageng, cinde/lancingan, blumbangan kampuh,  wedhungpasikon, belt (ukup), kepuh, and footwear (selop). Results indicate that the king clothes of Surakarta and Yogyakarta were not made to solely express symbolic meanings but also to differ identities of the throned kings. Changes on the shape of the throne (kuluk or panunggul), coat (sikepan  ageng bordiran bleggen), accesories, cinde pants (lancingan atau sarual), kampuh blumbangan with parang barong batik,  short sword (pasikon wedhung), keris, belt (ukup) a pair of clothes on the back, and footwear (selop), can be used to characterize the throned kings and thus identities of them.